Toxicological and safety evaluation of Nigella sativa lipid and volatile fractions in streptozotocin induced diabetes mellitus - Sultan, Muhammad Tauseef; Butt, Masood Sadiq; Karim, Roselina; Ahmad, Atif Nisar; Suleria, Hafiz Ansar Rasul; Saddique, Muhammad Suffyan (Elsevier, 2014)
Objective To evaluate the toxicological aspects of Nigella sativa (N. sativa) lipid and volatile fractions in streptozotocin induced diabetes mellitus. Methods National Institute of Health (NIH), Islamabad provided us thirty Sprague Dawley rats that were further divided into three groups, i.e. control, N. sativa lipid fraction (4%) and N. sativa volatile fraction (0.3%), respectively. The serological and haematological indices were evaluated at 4-week intervals during 56 d study. Results The results indicated that the diabetes mellitus imparted negative effects on various serological and haematological attributes. However, supplementation of the N. sativa lipid fraction and N. sativa volatile fraction ameliorated the adverse consequences of diabetes mellitus. The diabetes induced renal toxicity and imbalanced serum chemistry were slightly modulated by experimental diets. However, the impact of essential oil was more significant as compared to the fixed oil. Conclusions In a nutshell, experimental diets containing N. sativa lipid fraction and N. sativa volatile fraction are effective without having any toxicological effects, and experimental diets reduced toxicological and adverse consequences of diabetes mellitus.